Communication Methods of Muhammadiyah Gamping Special School (SLB) Teachers In Delivering Material to Students with Intellectual Disabilities - Rima Amanda; Aly Aulia (Jogjakarta Communication Conference (JCC), 2024)
Children with intellectual disabilities often face difficulties in communication and learning due to weaker intellectual functioning. SLB Muhammadiyah Gamping, located in the Sleman district of the Special Region of Yogyakarta, is one of the special schools in Jogja dedicated to educating children with special needs. The use of various communication methods in learning is essential for fostering effective teacher-student interactions. This qualitative descriptive research was conducted using interviews to collect data. The study found that Muhammadiyah Gamping Special School employs repetitive communication methods, supported by media tools such as Assmblr Edu, to enhance teaching and learning activities.